Exit interviews from two randomised placebo-controlled phase 3 studies with caregivers of young children with autism spectrum disorder - Hawken, Natalia; Falissard, Bruno; Choquet, Carl; Francois, Clement; Tardu, Jean; Schmid, Ramona (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction: Autism spectrum disorder (ASD) is characterised by difficulty with social communication and restricted, repetitive patterns of behaviour. This study aimed to improve understanding of the ASD patient experience with the treatment (bumetanide) regarding the changes in core symptoms and to assess changes considered as meaningful. To achieve this, qualitative interviews were conducted with caregivers of patients in 2 phase 3 clinical trials (NCT03715153; NCT03715166) of a novel ASD treatment.Methods: Caregivers were invited to participate in 1 interview after completion of the pivotal phase 3 study; and for those of them who continued treatment after study completion, a second interview was held at 3 months after trial completion. The interviews were conducted by qualitative researchers and followed a semi-structured interview guide. The interviews focused on patients' ASD symptoms and their impact on their daily life prior to enrolment, and on any symptom changes patients experienced during the trial.Results: Out of the 13 eligible patient's caregivers, eleven were interviewed up to 2 times at clinical sites in the UK, Spain, and Italy. The caregivers reported impairments in a wide range of skills: deficits in communication and social interaction; restricted, repetitive patterns of behaviour, interests, or activities; cognitive, emotional, and motor impairments. Compared to the before the trial initiation, caregivers also reported improvements in the following domains: communication, interaction with others, cognition, aggression, emotions, repetitive movements, eating and sleeping.The exit interviews provided a rich source of qualitative data, allowing a depeerdeeper understanding of caregivers' and patients' experience of the disease and allowing us to understand what constitutes a meaningful change. These data also helped to identify important experiences that may inform the patient-reported outcome measurement strategy for future trials in ASD.